International experience in the use of alternative energy sources (within the European Union) - Y. Zhuravel; O. Artemenko; N. Lytvyn; O. Yara; O. Uliutina (Law. Human. Environment)
The relevance of the chosen subject is due to the problem of the lack of conventional energy resources in the global and Ukrainian energy sectors. This problem is caused by a combination of external factors (outdated technologies, lack of oil, coal, and gas reserves) and internal factors, such as Russia’s military aggression against Ukraine, and its manipulative policy towards other countries, which encourages the European community to look for other options to ensure energy security. This gave a new urgency to the issue of activating the development of alternative energy. The purpose of the study is to analyse international experience in the use of alternative (renewable) energy and formulate conceptual methods and approaches to solving global energy problems. A combination of general scientific methods was used, primarily dialectical, analytical, concrete-sociological, and from special legal methods – comparative legal. The results obtained indicate that the use of alternative energy sources in the European Union countries will continue to develop in the future. Based on data from Regulatory Indicators for Sustainable Energy, it is confirmed that Denmark, Germany, and the Republic of Poland are currently the leaders in the use of renewable energy sources in the EU countries. The study analyses the successful experience of these countries in the use of renewable energy sources. It is concluded that there is a dynamic in the development of alternative energy sources in European countries, but in order for alternative energy sources to fully compete with conventional energy sources, it is necessary to maintain and regulate incentives for increasing the use of renewable energy sources at the national level. The practical value of the study lies in the fact that its results can serve as recommendations for increasing the share of alternative energy sources in Ukraine